Atrazine in municipal drinking water and risk of low birth weight, preterm delivery, and small-for-gestational-age status. Issue 6 (18th May 2005) - Villanueva, C M; Durand, G; Coutté, M-B; Chevrier, C; Cordier, S
Abstract : Background: Atrazine is a herbicide used extensively worldwide. Bioassays have shown that it is embryotoxic and embryolethal. Evidence of adverse reproductive outcomes from exposure in the general population is sparse. Aims: To evaluate the association between atrazine levels in municipal drinking water and the following adverse reproductive outcomes: increased risk of preterm delivery, low birth weight (LBW), and small-for-gestational-age (SGA) status. Methods: A total of 3510 births that took place from 1 October 1997, to 30 September 1998 were analysed. Atrazine measurements were available for 2661 samples from water treatment plants over the past decade. A seasonal pattern was identified, with atrazine peaking from May to September. The geometric mean of the atrazine level for this period was calculated for each water distribution unit and merged with the individual data by municipality of residence. Results: Atrazine levels in water were not associated with an increased risk of LBW or SGA status and were slightly associated with prematurity. There was an increased risk of SGA status in cases in which the third trimester overlapped in whole or in part with the May–September period, compared with those in which the third trimester occurred totally from October to April (OR = 1.37, 95% CI 1.04 to 1.81). If the entire third trimester took place from May to September, the OR was 1.54 (95% CI 1.11 to 2.13). Conclusions: Low levels of atrazine, a narrow exposure range, and limitations in the exposure assessment partly explain the lack of associations with atrazine. Findings point to the third trimester of pregnancy as the potential vulnerable period for an increased risk of SGA birth. Exposures other than atrazine and also seasonal factors may explain the increased risk.